Kesiapan Guru dalam Implementasi Kurikulum Merdeka - Wirnayanti, Wa Ode; Amaluddin, La Ode; Ati, Amniar (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2026)
The implementation of the Merdeka Curriculum is an adaptation process of the 2013 Curriculum that provides teachers with greater freedom to deliver learning materials creatively and enjoyably, in accordance with students' interests and talents. This study aims to determine the level of teacher readiness in implementing the Merdeka Curriculum at Senior High School 02 Baubau. The research method used is descriptive with a quantitative approach. The results show that of the 12 aspects of readiness analyzed, there are 10 aspects that are in the ready category, namely the design of the Learning Objective Flow, learning and assessment planning, the use and development of teaching tools, the planning and implementation of the Pancasila Student Profile Strengthening Project (P5), the application of student-centered learning, the integration of assessment with learning, learning according to the student's achievement stage, collaboration between teachers in curriculum development and learning, and the implementation of curriculum reflection and evaluation. Meanwhile, two other aspects are in the developing category, namely collaboration with students' parents and community involvement. Overall, the main obstacle felt by teachers in implementing the Merdeka Curriculum is the limited training received. The implications of this research emphasize the importance of strengthening teacher training and multi-stakeholder collaboration to support the successful implementation of the Merdeka Curriculum.